Mitochondrial ribosomal proteins (MRPs) of yeast. - Graack, H R (1998)
Mitochondrial ribosomal proteins (MRPs) are the counterparts in that organelle of the cytoplasmic ribosomal proteins in the host. Although the MRPs fulfil similar functions in protein biosynthesis, they are distinct in number, features and primary structures from the latter. Most progress in the eludication of the properties of individual MRPs, and in the characterization of the corresponding genes, has been made in baker's yeast (Saccharomyces cerevisiae). To date, 50 different MRPs have been determined, although biochemical data and mutational analysis propose a total number which is substantially higher. Surprisingly, only a minority of the MRPs that have been characterized show significant sequence similarities to known ribosomal proteins from other sources, thus limiting the deduction of their functions by simple comparison of amino acid sequences. Further, individual MRPs have been characterized functionally by mutational studies, and the regulation of expression of MRP genes has been described. The interaction of the mitochondrial ribosomes with transcription factors specific for individual mitochondrial mRNAs, and the communication between mitochondria and the nucleus for the co-ordinated expression of ribosomal constituents, are other aspects of current MRP research. Although the mitochondrial translational system is still far from being described completely, the yeast MRP system serves as a model for other organisms, including that of humans.